2005
DOI: 10.1007/11590323_47
|View full text |Cite
|
Sign up to set email alerts
|

Lets Come Together – Social Navigation Behaviors of Virtual and Real Humans

Abstract: Abstract. In this paper, we present a game-like scenario that is based on a model of social group dynamics inspired by theories from the social sciences. The model is augmented by a model of proxemics that simulates the role of distance and spatial orientation in human-human communication. By means of proxemics, a group of human participants may signal other humans whether they welcome new group members to join or not. In this paper, we describe the results of an experiment we conducted to shed light on the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In projective methods, participants are asked to hypothetically imagine a situation and indicate, either with pencil and paper or using dolls or figures, how they believe they or another individual would respond spatially in that scenario. Some of the techniques include the Comfortable Interpersonal Distance technique (Sinha and Nayyar 2000;Nechamkin et al 2003), simulation techniques (Bailenson et al 2003;Rehm, Andre, and Nischt 2005;Miwa and Hanyu 2006;Randell and Rowe 2006;Was, Gudowski, and Matuszyk 2006), and techniques using models and figures (Webb and Weber 2003). Projective techniques are simply not credible.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…In projective methods, participants are asked to hypothetically imagine a situation and indicate, either with pencil and paper or using dolls or figures, how they believe they or another individual would respond spatially in that scenario. Some of the techniques include the Comfortable Interpersonal Distance technique (Sinha and Nayyar 2000;Nechamkin et al 2003), simulation techniques (Bailenson et al 2003;Rehm, Andre, and Nischt 2005;Miwa and Hanyu 2006;Randell and Rowe 2006;Was, Gudowski, and Matuszyk 2006), and techniques using models and figures (Webb and Weber 2003). Projective techniques are simply not credible.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…Results of numerous studies confirm that humans involved in an F-formation keep more space around a group than the mere addition of single personal spaces [66][67][68]; thus, individuals stay away from social groups. Furthermore, research by Rehm et al [69] found that participants from high-contact cultures stand closer to a group of people compared with people from low-contact cultures.…”
Section: Avoiding Crossing Through Human Groups (Req 22)mentioning
confidence: 99%
“…Most of this work focuses on aspects such as gaze, facial expressions, and hand and arm gestures, rather than positioning and orientation in a group. There is some important work on authored presentation agents and avatars for human participants which take account of position in the modelling (Vilhjalmsson and Cassell, 1998;Rehm et al, 2005), but none of this work presents fully explicit algorithms for controlling the positioning and movement behavior of autonomous agents in dynamic conversations.…”
Section: Introductionmentioning
confidence: 99%